PERPUTARAN PIUTANG DALAM ASPEK KINERJA KEUANGAN PADA RUMAH SAKIT DI SURABAYA - Romilda Safa Maura Petrindasari; Rahmat Agus Santoso (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The aim of this research is to examine accounts receivable turnover in the financial performance aspect of hospitals in Surabaya. Accounts receivable turnover is calculated based on hospital financial report data collected from 2019 - 2022. A descriptive qualitative method was used in this research by interviewing three informants in accordance with research requirements. The data analysis method in this research uses the Miles and Huberman interactive model which consists of three activity flows that occur simultaneously, namely data reduction, data presentation and data verification. Based on the RTO (receivable turnover) graph, it shows increased efficiency in generating revenue from clinical and non-clinical operations. Hospitals can maximize the use of resources for higher revenues. This increase indicates better efficiency and productivity. on the other hand, the ACP (average collection period) graph is falling, meaning hospitals can collect receivables more quickly. this indicates more efficient financial governance, optimizing liquidity. this provides financial benefits, allowing hospitals to meet financial obligations more quickly and avoid the risk of payment arrears. Increasing RTO and decreasing ACP have a positive impact on financial stability and hospital operations.